Archäologische Forschungen in Teurnia Die Ausgrabungen in den Wohnterassen 1971-1978Die latènezeitlichen Funde vom Holzer Berg - Gugl, Christian (Österreichisches Archäologisches Institut, 2000)
The Claudian-era Municipium Teurnia, today's St. Peter in Holz, is situated four kilometers west of Spittal an der Drau (Carinthia, Austria). Along with Virunum, Celeia, luvavum and Aguntum, Teurnia counts as one of the oldest Roman cities in the province of Noricum. Due to its strategic location on the Drava River and at the intersection of two principal routes, namely the Drava Valley and the Tauern roads, Teurnia developed from a LaTène-period settlement to a Roman city, whose territory included large parts of Upper Carinthia and the Lungau in modern Salzburg. The assessment of La Tène period settlement activity in Teurnia is based solely on the finds assigned to the La Tène culture of Mokronog group centered in the south-east Alps. Continuous settlement in Teurnia can be proven from the late La Tène until the early Imperial period. A comparable trend can be seen at Celeia-Celje, where the initial Celtic hill settlement eventually developed into a Roman vicus in the valley. In contrast to this, the oldest identifiable settlement activity at Aguntum, luvavum and the Flavian municipium of Solva dates to the Augustan period, while Virunum was created as a new, planned provincial capital during the reign of the emperor, Claudius. The first settlement expansion in Teurnia is identifiable as early as the 3rd and 2nd decades of the first century BCE, as the first turf and timber constructions originated east of the 620m-high Holzer Mountain where habitation areas were located, built on serveral terraces on the eastern slope of the hill. Through the combined analysis of finds and results from the 1971-1978 excavations as well as several series of aerial photographs, the expansion and resulting monumentality of Teurnia's cityscape, after being awarded municipal status, is understandable. In this regard discussion continues as to whether the forum of the imperial-era city was actually located up on the hill, as proposed by R. Egger at the beginning of the last century, or in the lower town situated east of Holzer Mountain, as the preliminary interpretation of recent aerial photographs suggests. After a catastrophic fire in the early 3rd century CE this habitation area, a neighborhood with several prestigious homes and a public thermal bath furnished with high quality fittings such as stucco decoration, marble-cladding, wall paintings, window glass, and hypocaust heating technology, was not reconstructed. The abandonment of this settlement area may already have occurred before the Germanic invasions in the late 3rd century CE, maybe as a result of the Severan prospription measures.